Novel CircRNAs in Hub ceRNA Axis Regulate Gastric Cancer Prognosis and Microenvironment - Li, Xianghui; Li, Zhiyan; Liu, Ping; Ai, Shichao; Sun, Feng; Hu, Qiongyuan; Dong, Yuxiang; Xia, Xuefeng; Guan, Wenxian; Liu, Song (Frontiers in Medicine, 2021)
Gastric cancer (GC) is one of the most prevalent malignancies with unfavorable survival rate. Immunotherapy may contribute to better prognosis. However, several phase III trials failed. Circular RNA (CircRNA) is a novel type of non-coding RNA, plays vital roles in the progression of tumors. The expression and function of circRNA in GC immune microenvironment remain obscure. In this study, we utilized bioinformatic analysis to construct a circRNA/miRNA/mRNA network involved in the progression and prognosis of GC. CircRNA DYRK1A_017, circRNA FLNA_118, miR-6512-3p, miR-6270-5p, and VCAN were identified as key molecules in the hub regulatory axis. Dysregulation of this axis contributed to cancer-associated signaling pathways (EMT, NFκβ-TNFα signaling, and angiogenesis) and aberrant immune microenvironment (infiltration by tumor associated macrophage, regulatory T cell, and mast cell). More importantly, the immunosuppressive tumor microenvironment may reveal the mechanism of novel circRNAs in tumor and serve as the target of immunotherapy.